Deteksi Antibody Anti-Human Leukocyte Antigen (HLA) Kelas I Pada Donor Darah Wanita - Eti Herani; Ni Ken Ritchie; Heri Wibowo (MEDIA ILMU KESEHATAN, 2022)
Background: HLA class I is very polymorphic, if it enters the body of another person it will be considered foreign so that alloimmunization can occur by producing class I anti-HLA antibodies. These antibodies are found in individuals exposed to allogeneic cells due to transfusion, problems, and pregnancy. Female blood donors who have anti-HLA class I antibodies when donating blood and transfused to patients who have the appropriate HLA can cause a transfusion reaction. Research on class I anti-HLA antibodies in female blood donors in Indonesia is still very rare. This research is further to get an overview of class I anti-HLA antibodies in female blood donors.Objective: To determine the presence of potential class I anti-HLA antibodies in female donors.Methods: The subjects of this study were 30 female donors who had never been pregnant and 60 donors who had been pregnant and gave birth who donated their blood at UTD PMI DKI Jakarta. The collected samples were screened using the whole platelet ELISA method to detect platelet antibodies, namely anti-HPA and anti-HLA class I antibodies, followed by consulting anti-HLA class I antibodies with the MAIPA method.Results: Sixteen samples were detected to contain anti-platelet antibodies and 74 were negative. Identification of class I anti-HLA antibodies in 16 samples showed all negative results.Conclusion: Identification of 16 positive anti-platelet antibody samples in female donors did not show class I anti-HLA antibodies